THE EFFECT OF GRAFIC ORGANIZERS AND TEXT TYPES ON THE STUDENTS’ READING COMPETENCY AT SMAN 8 DENPASAR - IPY, Sudarmawan,; DK, Tantra,; AAIN, Marhaeni, (Universitas Pendidikan Ganesha, 2013)
Abstract This study attempted to find out the effect of graphic organizers and text types upon the students? reading competency. The subject of this study was the first grade students of SMAN 8 Denpasar. The independent variable was graphic organizers and conventional reading strategy (placebo), and the dependent variable wasreading competency. Text types was the moderator variable. The study was an experiment with posttest only control group design. The total number of population was 13 classes, which consisted of 586 students. From the population, two classes consisting of 92 students were used as samples. They were divided into two groups; experimental group and control group by multistage random sampling technique. Post-test was administered at the end of treatments and then analyzed by using two way ANOVA. The result of the analysis showed that: (1) There is an effect of graphic organizers upon the students? reading competency. (2) There is an interaction between graphic organizers and text types upon students reading competency Key words: graphic organizers, text types, and reading competency